2013
DOI: 10.4238/2013.november.7.5
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS14 gene polymorphism associated with knee osteoarthritis in Thai women

Abstract: ABSTRACT. Osteoarthritis (OA) is the most prevalent form of arthritis in the elderly. This disease is characterized by breakdown and loss of articular cartilage due to genetic, mechanical and environmental factors. Although the pathophysiology of OA is not completely known, several candidate genes have been reported to be associated with OA susceptibility. We assessed the association between genetic variation in the ADAMTS14 region and knee osteoarthritis susceptibility in the Thai population. The rs4747096 SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…Single nucleotide polymorphisms (SNPs) of ADAMTS14 have been associated with an increased risk of knee OA in two female cohorts32, 33. The enzyme may be differently regulated in murine OA models, since little regulation is observed in most murine microarray studies, other than reduced expression observed by Bateman et al.…”
Section: Adamtssmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) of ADAMTS14 have been associated with an increased risk of knee OA in two female cohorts32, 33. The enzyme may be differently regulated in murine OA models, since little regulation is observed in most murine microarray studies, other than reduced expression observed by Bateman et al.…”
Section: Adamtssmentioning
confidence: 99%
“…An augmented expression of this protease along with ADAMTS14 has also been described in OA [165,166]. In this regard, two polymorphisms have been identified in the ADAMTS14 gene associated with an increased risk of knee OA in woman [167,168]. However, the role played by these proteases in rheumatic pathologies is still quite unknown and more studies are needed.…”
Section: Procollagen N-propeptidasesmentioning
confidence: 99%
“…In one study, genetic variation in human ADAMTS5 did not seem to affect OA susceptibility (Rodriguez-Lopez et al, 2008); however, a separate investigation reached the opposite conclusion (Gu et al, 2013). Moreover, a non-synonymous single nucleotide polymorphism (SNP) of ADAMTS14 (rs4747096) has been shown to be associated with knee OA in Thai women (Poonpet et al, 2013). To the best of our knowledge, no study associating ADAMTS4 gene polymorphism with knee OA has been reported.…”
Section: Introductionmentioning
confidence: 97%